Evaluation of Foldable Tractor Roll-Over Protective Structures (ROPS) Clearance - Luke Martin (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Tractor rollovers are a leading cause of death in the agricultural industry. While rollovers continue to happen, Roll-Over Protective Structures (ROPS) have shown great ability to prevent or reduce the casualties and injuries associated with rollover events. One authority on the subject even goes so far as to claim that “that fatality rates due to tractor overturns could be reduced by a minimum of 71% if all tractors in the U.S. were equipped with ROPS,” (NIOSH, 2009). The potential of this promising statistic has been devalued slightly due to the misapplication of foldable ROPS by leaving the ROPS in the folded down position. Foldable ROPS provide a practical solution to various issues faced by tractor operators. However, a ROPS is not meant to be used in the folded down position, and there are engineering standards that should be used to determine if a folded down ROPS actually offers any protection. This study determined the operator protection provided by ROPS in the extended and the folded positions relative to the applicable engineering standards. To accomplish this, six different sized tractors with different ROPS were analyzed to determine the measurements required to calculate the protection that the tractor and ROPS combination provides in both positions, folded and extended. These calculations yielded results that show consistent trends among all tractors measured. With regards to the engineering standards, all tractors measured provide complete protection when in the upright, extended position and did not provide adequate protection when in the folded position. These results provide useful insights into engineering standards and recommendations.
Keywords: tractor; ROPS; agriculture; biosystems engineering; agricultural machinery